2006
DOI: 10.1103/physrevlett.96.208701
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic Dynamics on an Adaptive Network

Abstract: Many real-world networks are characterized by adaptive changes in their topology depending on the state of their nodes. Here we study epidemic dynamics on an adaptive network, where the susceptibles are able to avoid contact with the infected by rewiring their network connections. This gives rise to assortative degree correlation, oscillations, hysteresis, and first order transitions. We propose a low-dimensional model to describe the system and present a full local bifurcation analysis. Our results indicate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

33
915
2
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 814 publications
(972 citation statements)
references
References 21 publications
33
915
2
8
Order By: Relevance
“…Recently, it has been suggested that a different kind of strategy, implemented by the individuals themselves, could give surprisingly positive results in controlling disease spreading (Gross et al, 2006;Zanette and Risau-Gusman, 2008). The basic idea is that contact between non-infective and infective acquaintances must be systematically avoided.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been suggested that a different kind of strategy, implemented by the individuals themselves, could give surprisingly positive results in controlling disease spreading (Gross et al, 2006;Zanette and Risau-Gusman, 2008). The basic idea is that contact between non-infective and infective acquaintances must be systematically avoided.…”
Section: Introductionmentioning
confidence: 99%
“…If the social connectivity is nevertheless to be preserved, those broken links must be replaced by new connections. In the SIS (susceptible → infective → susceptible) epidemiological model analyzed by Gross et al (2006), it is susceptible agents who break contacts with their infective neighbors, what necessarily leads to the isolation of infective agents, and new connections are established only with other susceptible agents. Implicitly, this assumes that the epidemiological state of all agents is known to any other agent, irrespectively of whether they are connected or not.…”
Section: Introductionmentioning
confidence: 99%
“…Other works show that the dynamics of network topologies can introduce noise that fosters certain types of consensus processes 2,3 . Assuming that network topologies change in response to the dynamical process running on top of it, another line of research has studied adaptive networks, again highlighting that network dynamics have important consequences for dynamical processes 6,7 . Considering interactions in dynamic networks as a time series of events, a number of recent works focused on the question of whether observed inter-event times are consistent with the Poissonian distribution expected from a memoryless stochastic process.…”
mentioning
confidence: 99%
“…Analytic expressions for the ensuing degree distributions have been so far lacking, and their investigation has relied on numerical procedures [4][5][6][7]. As a consequence, the distributions' dependency on system parameters is difficult to infer and small parameter regions with counterintuitive topologies prone to be overlooked.Here, we revisit the adaptive contact process in dynamic equilibrium [11]. Using a compartmental approach [12], we obtain closed-form ensemble degree distributions dependent on a single external parameter, and show that a coarse-grained understanding of the distributions' shapes can be obtained self-containedly.…”
mentioning
confidence: 99%
“…In particular, the emergence of symmetric ensemble statistics from asymmetric dynamics can be explained. The framework's applicability to static networks as well as to other coevolutionary dynamics is also discussed.Model.-The contact process on an adaptive network models the spreading of a disease in a population without immunity, but with disease awareness [11]. The disease is transmitted along active links that connect infected I-nodes with susceptible S-nodes, letting the susceptible end switch to the Istate with rate p. Moreover, I-nodes recover to the S-state with rate r. Additionally, S-nodes evade infection by retracting active links with rate w and rewiring them to randomly selected S-nodes.…”
mentioning
confidence: 99%